The Moving of Indonesia’s Capital City and Its Legality Within Its Constitutional System - Farhan Farhan; Angelia Gunawan; Krisna Ananda Putra; Khanza Inas Az Zahra Fikry; Tengku Mahathir Mas'ud (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
The purpose of this study is to analyze the projected status of the Special Capital Region (DKI) Jakarta after the on-going move of Indonesia’s Capital City from Jakarta to Nusantara, and to analyze the legality status of the government’s decision regarding the move within Indonesia’s constitutional system. Through normative legal method, this study demonstrates that the status of DKI Jakarta as the capital city will change after the capital city move based on several articles in Law Number 3 of 2022 on Capital City; hence, the function and role of the capital city of the Republic of Indonesia will be transferred from DKI Jakarta to the National Capital City (IKN) after the president releases a presidential decree on the matter. Prior to the move, all positions, functions and roles of the capital city will remain in DKI Jakarta. Once the presidential decree related to the transfer of the capital city is released, the Law Number 29 of 2007 on the Provincial Government of Jakarta as the capital city of Indonesia will no longer be valid. However, Jakara’s function as an autonomous region will still apply. There are several steps that need to be done; firstly, compiling academic manuscript in drafting the academic text of Law Number 3 of 2022 on Capital City; secondly, conducting more discussions regarding Law Number 3 of 2022 on Capital City and the status of Law Number 29 of 2007 regarding the Provincial Government of Jakarta as the Capital City of Indonesia; thirdly, providing opportunity for public participation in the preparation and discussion in the making of Law Number 3 of 2022 on Capital City.